Appraising circular RNAs as novel biomarkers for the diagnosis and prognosis of gastric cancer: A pair‐wise meta‐analysis. Issue 8 (20th March 2020) - Chen, Hongjun; Wang, Kun; Pei, Dongxu; Xu, Haisheng
Abstract: Background: Circular RNAs (circRNAs), proven as single‐stranded closed RNA molecules, have been implicated in the onset and development of multiple cancers. This study aimed to summarize existing evidences regarding the clinicopathologic, diagnostic, and prognostic significances of circRNAs in gastric cancer (GC). Methods: Eligible studies were identified using online databases. The quality of the included studies was judged, and patients' clinical characteristics, diagnostic data, and overall survival (OS) were extracted from the electronic medical record. Fisher's method was adopted to determine P values for clinicopathologic features. The diagnostic and prognostic data from all included studies were merged. Results: Thirty eligible studies were comprised of 2687 GC patients were enrolled in the meta‐analyses. Altered expressions of circRNAs in GC tissues were significantly associated with worse clinicopathologic features. Abnormally expressed circRNAs yielded a pooled sensitivity of 0.76 (95% CI: 0.69‐0.81) and a specificity of 0.77 (95% CI: 0.70‐0.83) in distinguishing GC from noncancerous controls, which corresponded to an area under the curve (AUC) of 0.83. The survival analysis showed that the oncogenic circRNA signature could be an independent risk factor of OS (HR = 2.11, 95% CI: 1.60‐2.78, P  = .000). Patients with down‐regulated circRNAs (tumor suppressor genes) presented a significantly shorter OS time than those with high‐level circRNAs (HR = 0.33, 95% CI: 0.27‐0.42, P  = .000). Stratified analyses based on sample type, control source, circRNA expression status, and cutoff setting also produced robust results. Conclusions: CircRNAs may play an important role as potential diagnostic and prognostic biomarkers of GC.